2017
DOI: 10.1200/jco.2017.73.3238
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Validation of Enhancer of Zeste Homolog 2 Expression as an Independent Prognostic Marker in Localized Clear Cell Renal Cell Carcinoma

Abstract: PurposeEnhancer of zeste homolog 2 (EZH2), a chromatin remodeler, is implicated in the pathogenesis of clear cell renal cell carcinoma (ccRCC). However, the effect of EZH2 on outcomes in localized ccRCC is unclear, and molecular biomarkers are not currently integrated into prognostic models or adjuvant therapy trials.MethodsWe performed Cox regression to evaluate the association of tumor-based EZH2 gene and protein expression with survival in three independent cohorts: a cohort from The Cancer Genome Atlas (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 32 publications
(36 reference statements)
1
26
0
Order By: Relevance
“…Increasing evidences have indicated that aberrant expression of oncogenes or tumor suppressors are widely recognized as important factors in the carcinogenesis and progression of human carcinomas . In our study, we found that that WWOX mRNA and protein expression are decreased in HCC tissues and several cell lines when compared to adjacent tumor‐free tissues and normal liver cell lines, as determined by qRT‐PCR and Western blot.…”
Section: Discussionsupporting
confidence: 55%
“…Increasing evidences have indicated that aberrant expression of oncogenes or tumor suppressors are widely recognized as important factors in the carcinogenesis and progression of human carcinomas . In our study, we found that that WWOX mRNA and protein expression are decreased in HCC tissues and several cell lines when compared to adjacent tumor‐free tissues and normal liver cell lines, as determined by qRT‐PCR and Western blot.…”
Section: Discussionsupporting
confidence: 55%
“…The present study revealed that E-cadherin expression is less in tumor cells than in mTECs. As EZH2 and H3K27me3 expressions lead to transcriptional repression of tumor suppressor genes, including E-cadherin, and promote tumor progression 25,26 , it is anticipated that inhibition of EZH2 and H3K27me3 would enhance the sensitivity of tumor cells to cisplatin. Indeed, our data showed that treatment with 3-DZNeP potentiated the pro-apoptotic effect of cisplatin in tumor cells (H1299) that have a low level of E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologically, 3-DZNeP can promote degradation of EZH2 20 and subsequently reduce H3K27 me3 levels 21 . EZH2 has been shown to be overexpressed in many aggressive tumors 2224 , and H3K27me3 is responsible for the repression and heterochromatin formation of various tumor suppressor genes 25,26 . Pharmacological inhibition of EZH2 has been reported to be effective in animal models in the treatment of multiple cancers, such as myeloma 27 , leukemia 28 , lymphoma 29 , gastric cancer 30 , chondrosarcoma 31 , and lung cancer, especially NSCLC 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, multiple clinical managements, including surgery and radiation therapy, are available for patients with KIRC in an early stage; the 5-year survival rate after diagnosis has shown some improvement in recent years. However, the overall prognosis remains poor especially for patients with advanced disease, mostly due to lacking more effective therapeutics [ 4 ]. Thus, a more comprehensive understanding of the underlyingly molecular mechanism of KIRC is in urgent need for further development of novel treatment strategy against this disease.…”
Section: Introductionmentioning
confidence: 99%